Application of the PBL (Problem-Based Learning) Learning Model in Improving Front Roll Floor Gymnastics Ability at Class VII of SMPN 3 Gerung for the 2023-2024 academic year - Krisna, Dewa Ketut (Lembaga Penelitian dan Pendidikan Mandala, 2024)
The PBL Learning Model is a learning approach that is student-centered and focuses on problem solving. In the context of floor exercise abilities, especially the front roll sub-material. The approach used to improve front roll ability is Problem Based Learning (PBL). By using this approach, students are expected to be able to learn independently to find out good techniques through collaboration between their respective groups. So, from the overall process in this research, the total knowledge results were 2,060, the average knowledge was 79.2, the number of students who completed the study was 26, the percentage of students who completed was 100%, and the percentage of incomplete students was 0%. So, from the recapitulation data, the overall problem-based learning model for floor exercise on roll material has improved with the approach applied by teachers to students at SMPN 3 Gerung for the 2023-2024 academic year.